2018
DOI: 10.1038/s41419-018-1014-y
|View full text |Cite
|
Sign up to set email alerts
|

MiR-873-5p acts as an epigenetic regulator in early stages of liver fibrosis and cirrhosis

Abstract: Glycine N-methyltransferase (GNMT) is the most abundant methyltransferase in the liver and a master regulator of the transmethylation flux. GNMT downregulation leads to loss of liver function progressing to fibrosis, cirrhosis, and hepatocellular carcinoma. Moreover, GNMT deficiency aggravates cholestasis-induced fibrogenesis. To date, little is known about the mechanisms underlying downregulation of GNMT levels in hepatic fibrosis and cirrhosis. On this basis, microRNAs are epigenetic regulatory elements that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…Regarding their effect in the hepatocyte, both an upregulated A-SMase expression and ceramide content have been related to cell death [89] through activation of death receptors as fatty acid synthase (FAS) and TNFR1 [95]. The induction of necrosis in CCl 4 -treated mice, a fibrosis model widely studied [13,96], has been also correlated with an increase of ceramide content both in serum and liver [97]. Correlated with TNF, previously cited to deplete GSH levels in the cell during NASH, hepatocytes have been described to be more susceptible for cell death in that context [98,99].…”
Section: Ceramide and S1p Role In Fibrosis And Cirrhosis Developmentmentioning
confidence: 99%
“…Regarding their effect in the hepatocyte, both an upregulated A-SMase expression and ceramide content have been related to cell death [89] through activation of death receptors as fatty acid synthase (FAS) and TNFR1 [95]. The induction of necrosis in CCl 4 -treated mice, a fibrosis model widely studied [13,96], has been also correlated with an increase of ceramide content both in serum and liver [97]. Correlated with TNF, previously cited to deplete GSH levels in the cell during NASH, hepatocytes have been described to be more susceptible for cell death in that context [98,99].…”
Section: Ceramide and S1p Role In Fibrosis And Cirrhosis Developmentmentioning
confidence: 99%
“…A research by Ma et al reported that miR‐214 promoted the development of liver fibrosis via inducing the activation of HSCs . In addition, miR‐873‐5p has been demonstrated to be a marker for liver fibrosis and regulate the early stages of liver fibrosis . MiR‐351 has been confirmed to promote liver fibrosis via targeting the vitamin D receptor, and miR‐351 inhibition is recognized as a therapeutic intervention for fibrotic diseases .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that miRNAs are involved in the regulation of liver fibrosis (3840). let-7i, miR-342-3p, miR-188-5p and miR-34a are upregulated in CCl 4 -treated fibrotic livers compared with control samples, while miR-202, miR-378b and miR-378d are downregulated (41).…”
Section: Discussionmentioning
confidence: 99%